Right, Justice and Freedom in Hegel / Direito, Justiça e Liberdade em Hegel - Weber, Thadeu (Textos & Contextos (Porto Alegre), 2014)
This paper aims to explain the conception of justice in Hegel’s Philosophy of Right. It binds the conception to the idea of freedom in its different ways of determination. It starts from the notion of person of right and indicates the fundamental rights that derive from the expression of this legal capacity. It highlights the right of necessity as a right to make an exception in favor of itself aiming at the realization of justice. It shows how the administration of justice takes place through the Law in civic society.